Exploring Social Impact Through Virtual Reality Documentary : Findings from The Documentary Alverno (International Forum of Researchers and Lecturers, 2025)
This study examines the social impact of the virtual reality (VR) documentary Alverno, which explores the historical and emotional spaces of the Alverno Leprosy Hospital in Singkawang, Indonesia. Through a focus group discussion (FGD) with postgraduate students and academics at Institut Kesenian Jakarta, this research analyzes the effectiveness of narratology and ludology in creating immersive experiences that evoke caring and awareness about the social isolation of leprosy patients. Findings indicate that VR’s first-person storytelling and spatial audio design foster a strong sense of presence, enhancing emotional connections to marginalized histories. However, challenges in contextual understanding highlight the need for supplementary narrative elements. The study underscores VR’s potential as a tool for social education and cultural preservation, particularly in addressing stigma and forgotten histories, while identifying areas for technical and narrative improvement.